SELECTING A PROCESS FOR OIL AND GAS DEVELOPMENT RESERVE DEPOSITS HYDROCARBONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article presents information on the need to introduce clarifying elements to create models of heterogeneous geological objects that have a significant impact on the parameters of cone process calculations.